2022
DOI: 10.3390/ijms23084100
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of a Human Platelet Lysate-Loaded Keratin Hydrogel for Wound Healing Applications In Vitro

Abstract: One of the promising approaches to facilitate healing and regenerative capacity includes the application of growth-factor-loaded biomaterials. Human platelet lysate (hPL) derived from platelet-rich plasma through a freeze-thaw process has been used as a growth factor rich therapeutic in many regenerative applications. To provide sustained local delivery of the hPL-derived growth factors such as epidermal growth factor (EGF), the hPL can be loaded into biomaterials that do not degrade rapidly in vivo. Keratin (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 64 publications
0
5
0
Order By: Relevance
“…Furthermore, keratin hydrogels loaded with ciprofloxacin were developed to promote the healing of full-thickness excision wounds and prevent infection caused by Pseudomonas aeruginosa bacteria [ 148 ]. Human platelet lysate-loaded keratin hydrogels were also synthesized to exhibit sustained release of pro-regenerative growth factors essential for healing and enhancing cell proliferation without toxicity in vitro models [ 149 ]. Robert et al [ 150 ] utilized keratin-based wound dressing to treat a patient suffering from recessive dystrophic epidermolysis bullosa in 2012.…”
Section: Protein-based Nanoformulations In Normal and Diabetic Wound ...mentioning
confidence: 99%
“…Furthermore, keratin hydrogels loaded with ciprofloxacin were developed to promote the healing of full-thickness excision wounds and prevent infection caused by Pseudomonas aeruginosa bacteria [ 148 ]. Human platelet lysate-loaded keratin hydrogels were also synthesized to exhibit sustained release of pro-regenerative growth factors essential for healing and enhancing cell proliferation without toxicity in vitro models [ 149 ]. Robert et al [ 150 ] utilized keratin-based wound dressing to treat a patient suffering from recessive dystrophic epidermolysis bullosa in 2012.…”
Section: Protein-based Nanoformulations In Normal and Diabetic Wound ...mentioning
confidence: 99%
“…Keratin, a natural protein that is widely found in animal tissues such as wool, skin, nails, and feathers, and readily attainable from human hair, has received considerable attention in the field of hemostasis and wound healing in recent years. 7,8 This can be attributed to its low price, excellent biocompatibility, remarkable hemostatic abilities, improved cell adhesion properties, reduced immune response, and accelerated wound-healing properties. 9,10 It has been reported that keratin can promote hemostasis by significantly shortening the plasma coagulation lag time and increasing lateral fiber assembly and is able to maintain its activity under simulated coagulopathy conditions.…”
Section: Introductionmentioning
confidence: 99%
“…In an in vitro study, the release of epidermal growth factor (EGF) from the human platelet lysate-loaded KO hydrogel was controlled by changing the KO concentration. Also, because of the capacity of the KO hydrogel to support human dermal fibroblast proliferation, it is assumed to be a choice in wound healing applications . Delivering a variety of cells or bioactive agents using other types of keratin dressings like electrospun mats, , films, , and sponges , were also investigated.…”
Section: Introductionmentioning
confidence: 99%
“…Also, because of the capacity of the KO hydrogel to support human dermal fibroblast proliferation, it is assumed to be a choice in wound healing applications. 34 Delivering a variety of cells or bioactive agents using other types of keratin dressings like electrospun mats, 35,36 films, 35,37 and sponges 38,39 were also investigated. The functionalization with 35 or incorporation of 37 antimicrobial agents would enhance the capacity of biomaterials in fighting against infectious bacteria, and lead to more homogenous and natural re-epithelialization.…”
Section: Introductionmentioning
confidence: 99%